Survival of Eurasian lynx in the human‐dominated landscape of Europe - J. Premier; M. L. Bastianelli; J. Oeser; O. Anders; H. Andren; M. Aronsson; G. Bagrade; E. Belotti; C. Breitenmoser‐Würsten; L. Bufka; R. Černe; J. Červený; et al. (Conservation Biology, 2025)
Survival and cause‐specific mortality rates are vital for evidence‐based population forecasting and conservation, particularly for large carnivores, whose populations are often vulnerable to human‐caused mortalities. It is therefore important to know the relationship between anthropogenic and natural mortality causes to evaluate whether they are additive or compensatory. Further, the relation between survival and environmental covariates could reveal whether specific landscape characteristics influence demographic performance. We used telemetry data on 681 Eurasian lynx ( Lynx lynx ), a model apex predator with large spatial requirements, that were tracked across their European distribution. Through time‐to‐event analyses, we sought to determine the variables associated with differences in their survival. Illegal killing was the main cause of mortality (33.8%), and mortality rates were similar in protected and hunted populations (8.6% and 7.0% per year, respectively). Survival varied greatly across populations (70–95% per year). Across all study sites, higher hunting and anthropogenic mortality rates were partially compensated by lower rates of other mortality causes but not by natural mortality alone. Variation in survival depended on sex (female survival was 1.5 times greater than male survival) and seasonality (highest risk during hunting season and winter), and lower survival rates were correlated with higher human modification of landscapes at both coarse (home range composition) and fine (habitat use within home range) scales. Some variation in survival was driven by unobserved factors, which, given the high rates of human‐caused mortalities, including illegal killing, are of foremost concern. Due to the low natural mortality rates in protected and hunted populations, we conclude that anthropogenic causes of mortality are likely close to additive, such that maintaining or increasing refuge habitat with little human disturbance is critical to lynx conservation.

Long-term exposure to traffic noise and risk of incident colon cancer: A pooled study of eleven Nordic cohorts - Nina Roswall; Jesse D. Thacher; Mikael Ögren; Andrei Pyko; Agneta Åkesson; Anna Oudin; Anne Tjønneland; Annika Rosengren; Aslak H. Poulsen; Charlotta Eriksson; David Segersson; Debora Rizzuto; et al. (Environmental Research, 2023)

The spatial variation of O3, NO, NO2 and NO x and the relation between them in two Swedish cities - Annika Hagenbjörk; E. Malmqvist; K. Mattisson; Nilsson J. Sommar; L. Modig (Environmental Monitoring and Assessment, 2017)